2002
DOI: 10.1034/j.1600-0897.2002.1o059.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Antisperm Antibodies Bound to Sperm Surface in Male Immunological Infertility

Abstract: Some of the sperm-bound antibodies are associated with complement dependent sperm immobilizing antibodies, indicating that there exists a heterogeneity of sperm-bound antibodies. This result might be one of the reasons for the controversy about the relationship between ASA and immunological infertility in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Note that IgD and IgE isotypes are practically nonexistent in seminal fluid [24]. Compared to Shibahara et al [23], we found a lower incidence rates in the retrospective study but similar values in A. Laudat, L. Burc-Struxiano 7/11 OALib Journal the prospective study (with an increase in IgA-class antisperm antibody). The presence of immunoglobulins bound to different sections of spermatozoa has numerous repercussions on fertility.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Note that IgD and IgE isotypes are practically nonexistent in seminal fluid [24]. Compared to Shibahara et al [23], we found a lower incidence rates in the retrospective study but similar values in A. Laudat, L. Burc-Struxiano 7/11 OALib Journal the prospective study (with an increase in IgA-class antisperm antibody). The presence of immunoglobulins bound to different sections of spermatozoa has numerous repercussions on fertility.…”
Section: Discussionsupporting
confidence: 71%
“…Human antisperm autoimmunity appears to involve three classes of immunoglobulins. A study by Shibahara et al in 275 infertile men reported the following isotype-stratified incidence rates: 2.5% for IgG, 1.8% for IgA and 0.4% for IgM [23]. Note that IgD and IgE isotypes are practically nonexistent in seminal fluid [24].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, there is a need to examine the entry of other classes of antibody into the lumen of the reproductive ducts. For example, IgA and IgM as well as IgG have been found in human and boar semen [54,55], and in humans, prostatic fluid contains IgG [56] and the prostate gland secretes IgA [57][58][59][60]. It is possible that sufficient IgA may be secreted into accessory gland fluids for this purpose so that it is worthwhile examining mucosal as well as systemic immunization to raise the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…As for ASAs themselves, there is also diversity such as Ig classes of ASAs (22), the localization of the corresponding antigens against ASAs, and the biologic activity of ASAs bound to sperm surface in males (23). In some cases, it has been shown that ASAs bound to the sperm surface are sperm immobilizing antibodies; others were not (24).…”
Section: Discussionmentioning
confidence: 96%